FRI0475 TITLE: LUMBAR SPINE AND PROXIMAL FEMUR OSTEOPOROSIS DIAGNOSIS: REMS TECHNOLOGY IN A MULTICENTER CLINICAL STUDY. (June 2019) - Adami, Giovanni; Arioli, Giovanni; Bianchi, Gerolamo; Brandi, Maria Luisa; Caffarelli, Carla; Cavalli, Loredana; Matucci-Cerinic, Marco; Cianferotti, Luisella; Conversano, Francesco; Paola, Marco DI; Gatti, Davide; Girasole, Giuseppe; et al.
Abstract : Background: To date numerous quantitative methods to diagnose osteoporosis at peripheral sites have been developed. REMS (Radiofrequency Echographic Multi Spectrometry) is a non-ionizing instrument used to quantitatively evaluate bone mineral density at lumbar spine and femoral neck sites [1]. Objectives: To assess the accuracy of REMS in osteoporosis diagnosis at axial sites (lumbar spine and hip) compared with the gold standard, Dual-energy X-ray absorptiometry (DXA). Methods: We enrolled patients aged from 50 to 75 years and perfomed a total of 1, 699 and 1, 794 lumbar spine and proximal femur scans with REMS and DXA. A quality checks on DXA and REMS acquired data were performed through direct examination of scans by experienced operators. We investigated the agreement between the two techniques calculating: Pearson`s correlation coefficient ( r ), Standard Error of the Estimate (SEE) and efficiency (sensitivity and specificity) in identifying osteoporotic individuals (i.e. T-score ≤ -2.5). Results: We found a good linear correlation between REMS and DXA BMD estimation, Pearson coefficient r =0.938 for lumbar spine and r =0.933 for proximal femur ( p <0.001 for both). SEE values were 5.2% and 5.8% for lumbar spine and femoral site, respectively. In addition, REMS demonstrated a high sensitivity (92.9% and 92.3% for spine and femur) and specificity (93.5% for spine and 92.6% for femur) for the discrimination of osteoporotic patient. Moreover, considering together all the diagnostic classification categories (healthy, osteopenia and osteoporosis), the diagnostic agreement between REMS and DXA was 90.2% and 89.3% for lumbar spine and proximal femur sites, respectively. Conclusion: REMS exhibited a high sensitivity and specificity in identifying osteoporotic patients at lumbar spine or proximal femur sites compared with gold-standard DXA. REMS accurately diagnosed osteoporotic patients in clinical routine, at both lumbar spine and proximal femur sites, without using ionizing radiation. References: [1] Di Paola M, Gatti D, Viapiana O, et al. Osteoporos Int, 2018 Disclosure of Interests: Giovanni Adami: None declared, Giovanni Arioli: None declared, Gerolamo Bianchi: None declared, Maria Luisa Brandi: None declared, Carla Caffarelli: None declared, Loredana Cavalli: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen, Luisella Cianferotti Speakers bureau: Abiogen Pharma, Bruno Farmaceutici, Shire, Francesco Conversano Shareholder of: Francesco Conversano own stocks of Echolight Spa, Marco Di Paola: None declared, Davide Gatti Speakers bureau: Abiogen, Amgen, Janssen-Cilag, Mundipharma, Pfeizer, Giuseppe Girasole: None declared, Andrea Giusti: None declared, Stefano Gonnelli: None declared, Monica Manfedini: None declared, Maurizio Muratore: None declared, Ranuccio Nuti: None declared, Paola Pisani: None declared, Laura Quarta: None declared, Ombretta Viapiana Speakers bureau: Novartis, Abbvie, Eli-Lilly, Sanofi Genzyme